2022
DOI: 10.1101/2022.05.14.491875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Drosophila attP40 docking site and derivatives are insertion mutations of MSP300

Abstract: The ɸC31 integrase system is widely used in Drosophila to allow transgene targeting to specific loci. Over the years, flies bearing any of more than 100 attP docking sites have been constructed. One popular docking site, termed attP40, is located close to the Nesprin-1 orthologue MSP300 and lies upstream of certain MSP300 isoforms and within the first intron of others. Here we show that attP40 causes larval muscle nuclear clustering, which is a phenotype also conferred by MSP300 mutations. We also show that fl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…As in trans- Tango (Talay et al, 2017), the panneuronal components are inserted at the attP40 docking site in the genome. It is noteworthy that the attP40 docking site that has recently been shown to cause problems in the nervous system, especially when homozygous (Duan et al, 2022; Groen et al, 2022; van der Graaf et al, 2022). Therefore, we advise against using the panneuronal components in a homozygous configuration.…”
Section: Discussionmentioning
confidence: 99%
“…As in trans- Tango (Talay et al, 2017), the panneuronal components are inserted at the attP40 docking site in the genome. It is noteworthy that the attP40 docking site that has recently been shown to cause problems in the nervous system, especially when homozygous (Duan et al, 2022; Groen et al, 2022; van der Graaf et al, 2022). Therefore, we advise against using the panneuronal components in a homozygous configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large portion of the RNAi lines from the VDRC KK collection were found to produce phenotypes due to a secondary insertion and consequent ectopic expression of the tiptop gene (Green et al , 2014; Vissers et al , 2016). More recently, van der Graaf and colleagues reported that transgenes inserted in the commonly used attP40 landing site on the second chromosome can decrease the expression of Msp300, a member of the LINC complex, and hence lead to nuclear size, shape and positioning phenotypes (van der Graaf et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A large portion of the RNAi lines from the VDRC KK collection were found to produce phenotypes because of a secondary insertion and consequent ectopic expression of the tiptop gene ( Green et al, 2014 ; Vissers et al, 2016 ). More recently, van der Graaf and colleagues reported that transgenes inserted in the commonly used attP40 landing site on the second chromosome can decrease the expression of Msp300, a member of the LINC complex, and hence lead to nuclear size, shape, and positioning phenotypes ( van der Graaf et al, 2022 Preprint ).…”
Section: Discussionmentioning
confidence: 99%